Influence of Application of Cryopreserved Placental Cell Suspension on Indices of Peripheral Blood and Bone Marrow of Animals With Adjuvant Arthritis - Lutsenko, Elena D.; Ostankov, Maksim V.; Bondarovich, Nikolay A.; Goltsev, Anatoliy N. (Problems of Cryobiology and Cryomedicine, 2019)
In the model of adjuvant-induced arthritis in CBA/H mice there were investigated the gematological indices, circulating immune complexes (CIC) in peripheral blood, a number of hematopoietic stem cells: CD34+CD38– and CD117+ in bone marrow (BM) before and after applying either fresh or cryopreserved with various regimens placental cell suspension (PCS). PCS was cryopreserved with either 10% dimethyl sulfoxide or 10% propane diol saccharol. The maximum therapeutic effect was found after the introduction of fresh PCS (day 14) and suspension, cryopreserved with propane diol saccharol (day 28). The introduction of any from of PCS positively affected the erythrocyte sedimentation rate (ESR), CIC, nucleated cells in bone marrow, but the effect was manifested at different terms. The application of cryopreserved suspensions cont-ributed to the restoration of proliferative activity of hematopoietic stem cells. Depending on the cryopreservation regimen of the PCS, the properties of the injected suspension changed which aﬀected the recovery time of the number of CD117+-cells. Probl Cryobiol Cryomed 2019; 29(1): 028–043